Catalytic activity of nanostructured Au: Scale effects versus bimetallic/bifunctional effects in low-temperature CO oxidation on nanoporous Au - Wang, Lu-Cun; Zhong, Yi; Jin, Haijun; Widmann, Daniel; Weissmüller, Jörg; Behm, R. Jürgen (Beilstein Journal of Nanotechnology, 2013)
The catalytic properties of nanostructured Au and their physical origin were investigated by using the low-temperature CO oxidation as a test reaction. In order to distinguish between structural effects (structure–activity correlations) and bimetallic/bifunctional effects, unsupported nanoporous gold (NPG) samples prepared from different Au alloys (AuAg, AuCu) by selective leaching of a less noble metal (Ag, Cu) were employed, whose structure (surface area, ligament size) as well as their residual amount of the second metal were systematically varied by applying different potentials for dealloying. The structural and chemical properties before and after 1000 min reaction were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The catalytic behavior was evaluated by kinetic measurements in a conventional microreactor and by dynamic measurements in a temporal analysis of products (TAP) reactor. The data reveal a clear influence of the surface contents of residual Ag and Cu species on both O2 activation and catalytic activity, while correlations between activity and structural parameters such as surface area or ligament/crystallite size are less evident. Consequences for the mechanistic understanding and the role of the nanostructure in these NPG catalysts are discussed.
Keywords: AuAg alloy; AuCu alloy; CO oxidation; dynamic studies; kinetics; nanoporous Au (NPG) catalyst; oxygen storage capacity (OSC); temporal analysis of products (TAP)

(untitled) - Polarz, S.; Smarsly, B. (J. Nanosci. Nanotechnol., 2002)

(untitled) - Ding, Y.; Chen, M. (MRS Bull., 2009)

(untitled) - Erlebacher, J.; Aziz, M. J.; Karma, A.; Dimitrov, N.; Sieradzki, K. (Nature, 2001)

(untitled) - Zielasek, V.; Jürgens, B.; Schulz, C.; Biener, J.; Biener, M. M.; Hamza, A. V.; Bäumer, M. (Angew. Chem., Int. Ed., 2006)

(untitled) - Xu, C.; Su, J.; Xu, X.; Liu, P.; Zhao, H.; Tian, F.; Ding, Y. (J. Am. Chem. Soc., 2007)

(untitled) - Kameoka, S.; Pang Tsai, A. (Catal. Lett., 2008)

(untitled) - Déronzier, T.; Morfin, F.; Massin, L.; Lomello, M.; Rousset, J.-L. (Chem. Mater., 2011)

(untitled) - Li, R.; Sieradzki, K. (Phys. Rev. Lett., 1992)

(untitled) - Cortie, M. B.; Maaroof, A. I.; Smith, G. B. (Gold Bull., 2005)

(untitled) - Weissmüller, J.; Newman, R. C.; Jin, H.-J.; Hodge, A. M.; Kysar, J. W. (MRS Bull., 2009)

(untitled) - Xu, C.; Xu, X.; Su, J.; Ding, Y. (J. Catal., 2007)

(untitled) - Wang, L. C.; Jin, H.-J.; Widmann, D.; Weissmüller, J.; Behm, R. J. (J. Catal., 2011)

(untitled) - Wang, L. C.; Zhong, Y.; Widmann, D.; Weissmüller, J.; Behm, R. J. (ChemCatChem, 2012)

(untitled) - Wittstock, A.; Zielasek, V.; Biener, J.; Friend, C. M.; Bäumer, M. (Science, 2010)

(untitled) - Asao, N.; Hatakeyama, N.; Menggenbateer, X.; Minato, T.; Ito, E.; Hara, M.; Kim, Y.; Yamamoto, Y.; Chen, M.; Zhang, W.; Inoue, A. (Chem. Commun., 2012)

(untitled) - Asao, N.; Ishikawa, Y.; Hatakeyama, N.; Menggenbateer, X.; Yamamoto, Y.; Chen, M.; Zhang, W.; Inoue, A. (Angew. Chem., Int. Ed., 2010)

(untitled) - Haruta, M.; Kobayashi, T.; Sano, H.; Yamada, N. (Chem. Lett., 1987)

(untitled) - Haruta, M. (Catal. Surv. Jpn., 1997)

(untitled) - Schubert, M. M.; Hackenberg, S.; van Veen, A. C.; Muhler, M.; Plzak, V.; Behm, R. J. (J. Catal., 2001)

(untitled) - Haruta, M. (CATTECH, 2002)

Catalysis by Gold - Bond, G. C.; Louis, C.; Thompson, D. T. (Imperial College Press, 2006)

(untitled) - Aguilar-Guerrero, V.; Gates, B. C. (Catal. Lett., 2009)

(untitled) - Kotobuki, M.; Leppelt, R.; Hansgen, D. A.; Widmann, D.; Behm, R. J. (J. Catal., 2009)

(untitled) - Widmann, D.; Behm, R. J. (Angew. Chem., Int. Ed., 2011)

(untitled) - Widmann, D.; Liu, Y.; Schüth, F.; Behm, R. J. (J. Catal., 2010)

(untitled) - Remediakis, I. N.; Lopez, N.; Nørskov, J. K. (Angew. Chem., 2005)

(untitled) - Janssens, T. V. W.; Clausen, B. S.; Hvolbaek, B.; Falsig, H.; Christensen, C. H.; Bligaard, T.; Nørskov, J. K. (Top. Catal., 2007)

(untitled) - Chen, M. S.; Goodman, D. W. (Science, 2004)

(untitled) - Wittstock, A.; Neumann, B.; Schaefer, A.; Dumbuya, K.; Kübel, C.; Biener, M. M.; Zielasek, V.; Steinrück, H. P.; Gottfried, J. M.; Biener, J.; Hamza, A.; Bäumer, M. (J. Phys. Chem. C, 2009)

(untitled) - Wittstock, A.; Wichmann, A.; Biener, J.; Bäumer, M. (Faraday Discuss., 2011)

(untitled) - Xu, J.; Wang, Y.; Zhang, Z. (J. Phys. Chem. C, 2012)

(untitled) - Haruta, M. (ChemPhysChem, 2007)

(untitled) - Wittstock, A.; Biener, J.; Bäumer, M. (Phys. Chem. Chem. Phys., 2010)

(untitled) - Iizuka, Y.; Kawamoto, A.; Akita, K.; Daté, M.; Tsubota, S.; Okumura, M.; Haruta, M. (Catal. Lett., 2004)

(untitled) - Wang, A.-Q.; Liu, J.-H.; Lin, S. D.; Lin, T.-S.; Mou, C.-Y. (J. Catal., 2005)

(untitled) - Yen, C.-W.; Lin, M.-L.; Wang, A.; Chen, S.-A.; Chen, J.-M.; Mou, C.-Y. (J. Phys. Chem. C, 2009)

(untitled) - Moskaleva, L. V.; Röhe, S.; Wittstock, A.; Zielasek, V.; Klüner, T.; Neyman, K. M.; Bäumer, M. (Phys. Chem. Chem. Phys., 2011)

(untitled) - Liu, X.; Wang, A.; Li, L.; Zhang, T.; Mou, C.-Y.; Lee, J. F. (J. Catal., 2011)

(untitled) - Parida, S.; Kramer, D.; Volkert, C. A.; Rösner, H.; Erlebacher, J.; Weissmüller, J. (Phys. Rev. Lett., 2006)

(untitled) - Jin, H. J.; Parida, S.; Kramer, D.; Weissmüller, J. (Surf. Sci., 2008)

(untitled) - Trasatti, S.; Petrii, O. A. (Pure Appl. Chem., 1991)

(untitled) - Jin, H. J.; Kurmanaeva, L.; Schmauch, J.; Rösner, H.; Ivanisenko, Y.; Weissmüller, J. (Acta Mater., 2009)

(untitled) - Kahlich, M. J.; Gasteiger, H. A.; Behm, R. J. (J. Catal., 1997)

(untitled) - Leppelt, R.; Hansgen, D.; Widmann, D.; Häring, T.; Bräth, G.; Behm, R. J. (Rev. Sci. Instrum., 2007)

(untitled) - Gleaves, J. T.; Yablonskii, G. S.; Phanawadee, P.; Schuurman, Y. (Appl. Catal., A, 1997)

(untitled) - Tost, A.; Widmann, D.; Behm, R. J. (J. Catal., 2009)

(untitled) - Wertheim, G. K.; DiCenzo, S. B.; Youngquist, S. E. (Phys. Rev. Lett., 1983)

(untitled) - Pireaux, J.-J.; Liehr, M.; Thiry, P. A.; Delrue, J. P.; Caudano, R. (Surf. Sci., 1984)

(untitled) - Hoflund, G. B.; Hazos, Z. F.; Salaita, G. N. (Phys. Rev. B, 2000)

(untitled) - Liu, Y.; Bliznakov, S.; Dimitrov, N. (J. Electrochem. Soc., 2010)

(untitled) - Fu, Q.; Saltsburg, H.; Flytzani-Stephanopoulos, M. (Science, 2003)

(untitled) - Deng, W.; Carpenter, C.; Yi, N.; Flytzani-Stephanopoulos, M. (Top. Catal., 2007)

(untitled) - Haruta, M.; Tsubota, S.; Kobayashi, T.; Kageyama, H.; Genet, M. J.; Delmon, B. (J. Catal., 1993)

(untitled) - Boyen, H.-G.; Ethirajan, A.; Kästle, G.; Weigl, F.; Ziemann, P.; Schmid, G.; Garnier, M. G.; Büttner, M.; Oelhafen, P. (Phys. Rev. Lett., 2005)

(untitled) - Sandoval, A.; Aguilar, A.; Louis, C.; Traverse, A.; Zanella, R. (J. Catal., 2011)

(untitled) - Deng, L.; Hu, W.; Deng, H.; Xiao, S.; Tang, J. (J. Phys. Chem. C, 2011)

(untitled) - Shibata, T.; Bunker, B. A.; Zhang, Z.; Meisel, D.; Vardemann, C. F., II; Gezelter, J. D. (J. Am. Chem. Soc., 2002)

(untitled) - Li, Z. Y.; Wilcoxon, J. P.; Yin, F.; Chen, Y.; Palmer, R. E.; Johnston, R. L. (Faraday Discuss., 2008)

(untitled) - Alejo, L.; Lago, R.; Peña, M. A.; Fierro, J. L. G. (Appl. Catal., A, 1997)

(untitled) - Agrell, J.; Birgersson, H.; Boutonnet, M.; Melián-Cabrera, I.; Navarro, R. M.; Fierro, J. L. G. (J. Catal., 2003)

(untitled) - Matter, P. H.; Braden, D. J.; Ozkan, U. S. (J. Catal., 2004)

(untitled) - Dai, W.-L.; Sun, Q.; Deng, J.-F.; Wu, D.; Sun, Y.-H. (Appl. Surf. Sci., 2001)

(untitled) - Ferrando, R.; Jellinek, J.; Johnston, R. L. (Chem. Rev., 2008)

(untitled) - Schumacher, B.; Denkwitz, Y.; Plzak, V.; Kinne, M.; Behm, R. J. (J. Catal., 2004)

(untitled) - Denkwitz, Y.; Schumacher, B.; Kučerová, G.; Behm, R. J. (J. Catal., 2009)

(untitled) - Sault, A. G.; Madix, R. J.; Campbell, C. T. (Surf. Sci., 1986)

(untitled) - Saliba, N.; Parker, D. H.; Koel, B. E. (Surf. Sci., 1998)

(untitled) - Deng, X.; Min, B. K.; Guloy, A.; Friend, C. M. (J. Am. Chem. Soc., 2005)

(untitled) - Min, B. K.; Alemozafar, A. R.; Pinnaduwage, D.; Deng, X.; Friend, C. M. (J. Phys. Chem. B, 2006)

(untitled) - Grant, R. B.; Lambert, R. M. (Surf. Sci., 1984)

(untitled) - Campbell, C. T. (Surf. Sci., 1985)

(untitled) - Rehren, C.; Isaac, G.; Schlögl, R.; Ertl, G. (Catal. Lett., 1991)

(untitled) - Lee, S. Y.; Mettlach, N.; Nguyen, N.; Sun, Y. M.; White, J. M. (Appl. Surf. Sci., 2003)

(untitled) - Soares, J. M. C.; Bowker, M. (Appl. Catal., A, 2005)

(untitled) - Gottfried, J. M.; Schmidt, K. J.; Schroeder, S. L. M.; Christmann, K. (Surf. Sci., 2003)

(untitled) - Baker, T. A.; Xu, B.; Xiaoying, L.; Kaxiras, E.; Friend, C. M. (J. Phys. Chem. C, 2009)

(untitled) - Schaefer, A.; Ragazzon, D.; Wittstock, A.; Walle, L. E.; Borg, A.; Bäumer, M.; Sandell, A. (J. Phys. Chem. C, 2012)

(untitled) - Green, I. X.; Tang, W.; Neurock, M.; Yates, J. T. (Science, 2011)

(untitled) - Groß, A. (J. Phys.: Condens. Matter, 2009)

(untitled) - Behm, R. J. (Z. Phys. Chem., 2009)

(untitled) - Moskaleva, L. V.; Zielasek, V.; Klüner, T.; Neyman, K. M.; Bäumer, M. (Chem. Phys. Lett., 2012)

(untitled) - Liu, X.; Wang, A.; Zhang, T.; Su, D. S.; Mou, C.-Y. (Catal. Today, 2011)

(untitled) - Haruta, M.; Daté, M. (Appl. Catal., A, 2001)

(untitled) - Fujitani, T.; Nakamura, I. (Angew. Chem., Int. Ed., 2011)